WAR AND PRISONERS OF WAR - Nemat Sobirovich Sobirov (Journals Park Publishing, 2023)
In this article detailed information was given about prisoners of the World War I which came to the Fergana valley, their history, lives and activities at the period of 6-7 years and returning their Motherlands.
Keywords: war prisoners, World War I, zone, officer, under-officer, feldfebel, Austria, Hungary, Germany’s war prisoners, evakpunkt, distinct, tenpin, Volos, coal mine, oil mine, hospital, castle.